Applying AlAfnan Taxonomy to English Composition Courses: Structuring Learning Outcomes for Effective Teaching - AlAfnan, Mohammad Awad; MohdZuki, Siti Fatimah; AlAfnan, Shefa Mohammad (Journal of Ecohumanism, 2024)
The article explores the significance of adopting AlAfnan’s (2024a) educational taxonomy in teaching composition courses. Moving beyond the traditional focus on technical writing skills, this framework incorporates foundational knowledge, critical thinking, ethical reasoning, practical application, creativity, and adaptability. The aim is to cultivate proficient writers and holistic communicators equipped to navigate the complexities of the dynamic 21st-century landscape. The foundation of the educational taxonomy lies in acknowledging that composition courses are more than exercises in mastering mechanics; they represent a journey into ideas. By infusing foundational knowledge and comprehension, students gain a profound understanding of the subjects they engage with, ensuring clarity and coherence in their expression. Evaluation and synthesis go beyond the transmission of information to foster intellectual rigor and depth in student writing. Integrating ethical and moral reasoning into the taxonomy prompts students to consider the societal implications of their language choices, instilling a sense of responsibility in communication. Practical application and strategic thinking are deemed indispensable for effective writing. The framework prepares students for the diverse challenges of the professional world to transcend the boundaries of academic writing. Creativity and innovation are embraced to create an environment where original ideas and innovative writing approaches are encouraged and celebrated. In recognition of the rapid changes characterizing the modern era, AlAfnan’s educational taxonomy incorporates lifelong learning and adaptability elements. This ensures that students view writing skills as dynamic tools requiring continuous refinement, cultivating a mindset essential for success in an ever-evolving global environment. The achievement of the learning outcomes in this study shall transform composition courses into transformative experiences that shape students into adept communicators prepared for the multifaceted demands of a rapidly evolving world.